An RSA-Like Scheme for Multiuser Broadcast Authentication in Wireless Sensor Networks - Chen-Yang Cheng; Iuon-Chang Lin; Shu-Yan Huang (International Journal of Distributed Sensor Networks)
For network users roaming in a wireless sensor network (WSN), they can broadcast queries to WSNs to obtain the latest sensed data from sensor nodes using their mobile devices. In such a scenario, each sensor node has to verify the validity of every query sent from users. In this paper, RSA-like public key cryptography is employed to design a mechanism for multiuser broadcast authentication in WSNs. Within the proposed scheme, the use of certificates becomes optional. When users broadcast queries to WSNs, each sensor node can verify every query immediately without buffering any one. As a result, the energy cost for verifying a query by a sensor node is very small. Furthermore, our scheme provides enough scalability and security. The quantitative analyses show that our scheme is efficient in terms of storage and computational overheads.